2006
DOI: 10.1088/0957-0233/17/5/s44
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured optical fibre sensors for breathing airflow monitoring

Abstract: A nanostructured optical fibre-based thin film sensor was designed for non-invasive, fast and reliable monitoring of respiratory airflow. Molecular-level self-assembly processing method was used to form multi-layered inorganic nanocluster and polymer thin films on the distal ends of optical fibres to form such sensors. In order to optimize the sensing performance, an analytical model based on the condensation of exhaled water vapour on the coating surface was established for the breathing analysis. By varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…7, which was formed by placing alternating multilayer thin films of polymers and inorganic nanoclusters on the cleaved end of a single-mode fiber (SMF). [78][79][80] However, the patient is required to wear a mask with built-in sensors, which presents a notable obstacle of the PCF-and FP-based fiber-optic interferometers for respiration monitoring. Table 3 lists the major results obtained using these devices.…”
Section: Interferometric Fiber-optic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, which was formed by placing alternating multilayer thin films of polymers and inorganic nanoclusters on the cleaved end of a single-mode fiber (SMF). [78][79][80] However, the patient is required to wear a mask with built-in sensors, which presents a notable obstacle of the PCF-and FP-based fiber-optic interferometers for respiration monitoring. Table 3 lists the major results obtained using these devices.…”
Section: Interferometric Fiber-optic Sensorsmentioning
confidence: 99%
“…As above 1b.I; [78][79][80] Fabry-Pérot interferometer inside plastic tube; RR Tests were carried out using a simulated breathing flow system, with relation to thin-film refractive indices and thickness; no data on sensor efficiency field. Thus, the receiving section of the sensor serves as a detector for the radiation propagated within the MMF section, i.e., the measurement head.…”
Section: Sensors In Modalmetric Configurationmentioning
confidence: 99%
“…It was concluded that both the FBG and LPG techniques can be applied for hydrogen sensing, but the sensitivity of LPG sensor was higher by about a factor 500 than that of FBG. A zeolite thin film-based fiber optic Fabry-Perot interferometric (FPI) sensor for in situ detection of dissolved organics in water was described in [15]. It was reported that the described sensor had different responses (time and amplitude) towards different organic molecules, with an estimated detection limit of 2 ppm for toluene, 5 ppm for 2-propanol, and 1,000 ppm for methanol.…”
Section: Fiber Optical Chemical Sensorsmentioning
confidence: 99%
“…Fast response and recovery time are critical for this kind of measurements. Different types of breathing sensors have been experimentally reported: the most relevant ones are devices based on microstructured fiber [34], macrobending [35], medical textiles in which Bragg and time reflectometry sensors are embedded [36], devices based on nanostructured fibers [37] or plastic optical fiber (POF) [38].…”
Section: Introductionmentioning
confidence: 99%